Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0047830
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 Associates with Diabetes but Not Established Cardiovascular Risk Factors: A New Inflammatory Pathway of Relevance to Diabetes?

Abstract: Preliminary data mostly from animal models suggest the sST2/IL-33 pathway may have causal relevance for vascular disease and diabetes and thus point to a potential novel inflammatory link to cardiometabolic disease. However, the characterisation of sST2 levels in terms of metabolic or vascular risk in man is completely lacking. We sought to address this gap via a comprehensive analysis of risk factor and vascular correlates of sST2 in a cross-sectional study (pSoBid). We measured sST2 in plasma in 639 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 35 publications
(60 reference statements)
8
56
0
Order By: Relevance
“…Nevertheless, to the current date, it remains unclear whether sST2 is causally and directly involved in carcinogenesis or whether it is to be seen as a marker of concomitant inflammation or tissue injury. Evidence for that arises from elevated levels of sST2, which are also found in nontumor conditions, e.g., allergy, atopy, multiple sclerosis, inflammatory bowel diseases, and recently even in cardiovascular disease [30][31][32]. The significant correlation of the sST2 serum concentration with the levels of AST and CRP in our study indicates that sST2 is associated with liver injury and (hepatic) cell death as well as the systemic inflammatory response.…”
Section: Il-33/sst2 Ratiosupporting
confidence: 60%
“…Nevertheless, to the current date, it remains unclear whether sST2 is causally and directly involved in carcinogenesis or whether it is to be seen as a marker of concomitant inflammation or tissue injury. Evidence for that arises from elevated levels of sST2, which are also found in nontumor conditions, e.g., allergy, atopy, multiple sclerosis, inflammatory bowel diseases, and recently even in cardiovascular disease [30][31][32]. The significant correlation of the sST2 serum concentration with the levels of AST and CRP in our study indicates that sST2 is associated with liver injury and (hepatic) cell death as well as the systemic inflammatory response.…”
Section: Il-33/sst2 Ratiosupporting
confidence: 60%
“…Serial changes in sST2 over time predict outcomes independent of natriuretic peptides, suggesting its potential use in monitoring heart failure,13 or guiding therapy for acute coronary syndromes 14. In the general population, sST2 levels were associated with cardiovascular death and heart failure in the Framingham cohort and mortality in Framingham and Dallas Heart Studies4 15 and also with incident diabetes 16. Unlike NT-proBNP, sST2 levels are not related to age, prevalent heart failure, atrial fibrillation, Body Mass Index, or renal function in studies spanning those at high risk, and general populations 4 5 10 15 17…”
Section: Introductionmentioning
confidence: 98%
“…So, we thought that IL-33 levels are higher because of diabetes mellitus independent from kidney injury because Miller et al showed that soluble ST2 associates with diabetes mellitus. 10 Also Bao et al reported that IL-33 levels do not differ between patients with chronic kidney disease and healthy individuals; in addition Il-33 levels are similar in three stages of kidney injury when they are divided into three groups according to their GFR. 11 In another study, the IL-33 levels did not differ between multiple myeloma patients with and without kidney failure.…”
Section: Discussionmentioning
confidence: 99%